A short review on queuing theory as a deterministic tool in sustainable telecommunication system. (2021) - Afolalu, S.A.; Ikumapayi, O.M.; Abdulkareem, A.; Emetere, M.E; Adejumo, O.
Abstract: Telecommunication mechanisms have been conceptualized simply as links between two points to send signals. Telecommunication networks are, at present, characterized by clusters of nodes, interconnecting nodes where information is processed and correctly addressed to the output links. The transmission of messages was assisted by the first telecommunication networks for telegraphy. Mobile phone networks were then built to build a physical call circuit set up to connect the source and destination for the entire duration of the conversation. The networks of today are digital and are focused on the dissemination of signals arranged in blocks, called packets, which are either routed independently along the nodes or transmitted from source to destination through a virtual path. On the basis of the network hierarchy, transmission media are usually distinguished. When a customer of a company has any kind of issue, their first contact with the company is the call center. They give feedback of their issues to the call center and the call center's quality service is so important because the service would determine if the customer's issue is resolved and if the customer would continue to do business with the company afterwards. Deciding an optimum number of operators using key performance index is an important factor in optimizing a communication system. Research carried out show that this optimization can be made using queuing theory approach. A practical application of optimizing a call center using stochastic queuing approach is studied in this review. From the research, the optimal number of operators for the call center was determined for various peak periods considering four performance index measures. The information gathered shown the importance of using queuing theory model as a deterministic tool for optimizing a communication system.